Dynamic research of piston/piston assembly in labyrinth reciprocating compressor. (August 2019) - Zhang, Wenshan; Zhang, Zhao; Qian, Lv; Feng, Quanke; Wu, Weifeng
Abstract: The piston of labyrinth reciprocating compressor is often in the eccentric running state during operation, which leading to serious gas leakage and reduced compressor volume efficiency. To optimize the performance of labyrinth reciprocating compressor, the main reasons of piston eccentric operation are analyzed in detail in this paper. Based on the theory of multi-body dynamic and influence of piston bending and vibration, a rigid-flexible coupling multi-body virtual simulation model of piston/piston rod assembly is established by using numerical analysis software. The factors causing eccentric running of piston in cylinder are investigated and the eccentric running track of piston in cylinder and its dynamic characteristics are obtained.